Kepemimpinan Transaksional dan Transformasional - Fadillah Ramadhani Asiri; Rabiatul Alya; Rianti Simarmata; Yusawinur Barella (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This research examines the influence of transactional and transformational leadership on honesty, effective leadership, integrity. Transactional leadership focuses on rewards and punishments to achieve goals, whereas transformational leadership inspires and motivates followers to go beyond personal interests. Through surveys and statistical analysis, the results show that transformational leadership more significantly increases performance, job satisfaction, and organizational commitment than transactional leadership. However, transactional leadership remains relevant in situations that require structure and tight control. A combination of these two styles is recommended for optimal results in various organizational contexts.